Can evidence-based medicine and clinical quality improvement learn from each other?. (30th March 2011) - Glasziou, Paul; Ogrinc, Greg; Goodman, Steve
Abstract : The considerable gap between what we know from research and what is done in clinical practice is well known. Proposed responses include the Evidence-Based Medicine (EBM) and Clinical Quality Improvement. EBM has focused more on 'doing the right things'—based on external research evidence—whereas Quality Improvement (QI) has focused more on 'doing things right'—based on local processes. However, these are complementary and in combination direct us how to 'do the right things right'. This article examines the differences and similarities in the two approaches and proposes that by integrating the bedside application, the methodological development and the training of these complementary disciplines both would gain.